Pelatihan metode membaca Al-Qur’an berbasis Qiraah Asy-Syafi’i bagi Mahasiswa FIK UNM - Muhammadong Muhammadong; Arifuddin Usman; Hasbi Ansyari (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
The aim to be achieved in this program was to providetraining to FIK students about the qiraah-based reading methodof Al-qur'an. Therefore, if the students finish their study, theycan implement their knowledge about Qur’an in the community.Basically, religious study groups at the Faculty of SportSciences, UNM already understand the Qur'an. However, thetraining was still needed to be done in order to deepen themethods used so the students could be better master the contentsof the Al-Qur'an. The specific target to be achieved in thistraining program was the students could find out about Al-Qur'anreading so that they could read Al-Qur'an well and couldimplement it in the community. The method used in this trainingincluded: 1. Harfiyyah Method, where the teacher started thelesson by teaching hija'iyyah letters one by one, 2. Sautiyyahmethod. In this method the letters were taught to students as theorder. This teaching began by teaching the letters of fathah, thenthe letters with dhammmah, the letters with kasrah and sukun.After that, then move on to the letter lesson based on FathataniTanwan, 3. Syllable method. In this method students first learnedsyllables, then learned words made up of these syllables. Beforeteaching syllables, the students should be taught about madletters, 4. The Word Method. This word method has apsychological foundation that assumes that students know thingsthat are common first, then develops to know the parts of thegeneral. The proposed activity plan consisted of two mainactivities, namely (1) Training activities: this activity is carriedout by providing material on the qiraah-based Al-Qur'an readingmethod so that students can understand how to read the Qur'anwell; (2) Skill Activity: this activity is done by practicing readingthe Qur'an so that the students can practice the Qur'an readingwell and they can implement it to the community.